Impact of catchment-derived nutrients and sediments on marine water quality on the Great Barrier Reef: An application of the eReefs marine modelling system. (June 2021) - Baird, Mark E.; Mongin, Mathieu; Skerratt, Jennifer; Margvelashvili, Nugzar; Tickell, Sharon; Steven, Andrew D.L.; Robillot, Cedric; Ellis, Robin; Waters, David; Kaniewska, Paulina; Brodie, Jon
Abstract: Water quality of the Great Barrier Reef (GBR) is determined by a range of natural and anthropogenic drivers that are resolved in the eReefs coupled hydrodynamic - biogeochemical marine model forced by a process-based catchment model, GBR Dynamic SedNet. Model simulations presented here quantify the impact of anthropogenic catchment loads of sediments and nutrients on a range of marine water quality variables. Simulations of 2011–2018 show that reduction of anthropogenic catchment loads results in improved water quality, especially within river plumes. Within the 16 resolved river plumes, anthropogenic loads increased chlorophyll concentration by 0.10 (0.02–0.25) mg Chl m −3 . Reductions of anthropogenic loads following proposed Reef 2050 Water Quality Improvement Plan targets reduced chlorophyll concentration in the plumes by 0.04 (0.01–0.10) mg Chl m −3 . Our simulations demonstrate the impact of anthropogenic loads on GBR water quality and quantify the benefits of improved catchment management.